Genome Sequence of the Leaf-Colonizing Bacterium Bacillus sp. Strain 5B6, Isolated from a Cherry Tree - Kim, Byung Kwon (American Society for Microbiology, 2012)
Plant growth-promoting bacteria colonize various habitats, including the phyllosphere. Here, we present the high-quality draft genome sequence of Bacillus sp. strain 5B6, which was isolated from the leaf of a cherry tree. The 3.9-Mb genome uncovers its potential for understanding the nature of leaf colonization as well as antibiosis against plant pathogens.